Konserwacja i restauracja malowidła Anioł zwiastujący Joachimowi narodziny Marii z cyklu polichromii ściennych Wacława Taranczewskiego w kościele pw. św. Anny w Poznaniu - Lament-Kosińska, Angelika (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2016)
The polychromes series in the church of St. Anna in Poznan is an example of monumental realizations by one of the famous contemporary polish artist, Waclaw Taranczewski (1903–1987). However, the present polychromes’ state of preservation is very bad. The aim of this article is to present the restoration process performed on the wall painting “Angel heralding the birth of Mary to Joachim” which is one of the scenes from polychromes series in the St. Anna’s church. The works were intended to preserve the painting by consolidation and restoration of its original layers. Whole process included a disinfection, surface cleaning, consolidation, removal of overpainting, filling and inpainting by pin pointing. This complex restoration was held in 2014 and was the first step to preserve other scenes in this polychromes series